Implementasi Maqasid Al-Syariah dalam Pembelajaran Fikih: Studi pada Siswa SMA N 1 Purwokerto - Lutfiana, Annisa; Yusuf, Enjang Burhanudin (Lembaga Yasin AlSys, 2025)
The implementation of Maqasid Shariah in fiqh instruction at SMA N 1 Purwokerto remains limited, even though focusing on the objectives of Islamic law has the potential to strengthen students’ character and contextual understanding of Islamic values. This study aims to explore the extent to which the concept of Maqasid Shariah is integrated into the fiqh learning process, using a descriptive-analytical qualitative approach with a sample of six teachers and eight students deemed representative. Data were collected through literature review and semi-structured interviews, and analyzed using thematic analysis to uncover patterns of implementation, challenges, and educational outcomes. The findings show that fiqh teachers have implemented the values of maqasid al-dharuriyyah (essential benefits), al-hajiyyah (needs), and al-tahsiniyyah (enhancements) through the development of case discussion materials, social service assignments, and reflective applications of Islamic law in daily life. These efforts have been shown to enhance students’ tolerance, sense of responsibility, and social awareness, as well as deepen their critical understanding of fiqh. The theoretical implications of this study enrich the literature on Maqasid Shariah-based fiqh pedagogy and emphasize the importance of goal-oriented Islamic legal education in character development. Practically, the study recommends revising the Islamic Religious Education (Pendidikan Agama Islam or PAI) curriculum to include Maqasid Shariah modules, training teachers in contextual teaching methods, and developing case-based instructional materials aligned with maqasid. These findings open avenues for further research on the effectiveness and adoption of Maqasid Shariah at various levels and contexts of Islamic education.